A Case-Based Review of Cerebral Venous Infarcts With Perfusion Imaging and Comparison to Arterial Ischemic Stroke - Li, Anna Y.; Tong, Elizabeth; Yedavalli, Vivek S. (Frontiers in Radiology, 2021)
Cerebral venous thrombosis (CVT) and cerebral venous infarcts (CVI) are diagnostic dilemmas secondary to their rarity, non-specific symptomatology at presentation, and variable imaging features. CVT is a relatively infrequent entity – seen in only 0.5 – 2% of stroke cases – and progresses to CVI in 50% of cases. CVT is particularly prevalent in the younger adult population and among women of childbearing age. It is a potentially life-threatening disease with devastating neurological complications if not addressed in a timely manner. However, when treated promptly, CVT has the potential for a more reversible course and favorable prognosis than arterial ischemic infarcts (AIS). The pathophysiology of cerebral venous infarcts (CVI) is distinct from that of AIS and is closely related to its potentially reversible nature. Familiarity with the normal and variant venous anatomy as well as the evolution of imaging findings is crucial in establishing diagnostic confidence. In recent years, the use of MR perfusion imaging (MRP) and arterial spin-labeling (ASL) have become more widespread in the imaging of AIS; similarly, MRP and ASL can potentially aid in diagnosing CVT/CVI. This review presents a case-based overview focusing on the classic imaging characteristics of CVT and CVI with select cases including bolus MRP and/or ASL findings in the adult population. To date, no studies have investigated ASL in CVI and both bolus MRP and ASL together in CVT/CVI, which would be a potential area of interest to explore in future studies.